The diary of Manu Gandhi, 1943-1944 - Manubahana Gāndhī (OUP, 2019)
Manu Gandhi, M.K. Gandhi’s grand-niece, joined him in 1943 at the age of fifteen. An aide to Gandhian ailing wife Kasturba in the Aga Khan palace prison in Pune, Manu remained with him until his assassination. She was a partner in his final yajna, an experiment in Brahmaputra, and his invocation of Rama at the moment of his death. Spanning two volumes, the Diary of Manu Gandhi is a record of her life and times with M.K. Gandhi between 1943 and 1948. Authenticated by Gandhi himself, the meticulous and intimate entries in the Diary throw light on Gandhi’s life as a prisoner and his endeavour to establish the possibility of collective non-violence. They also offer a glimpse into his ideological conflicts, his efforts to find his voice, and his Lonely pilgrimage to Noakhali during the riots of 1946. The first volume (1943–44) chronicles the spiritual and educational pursuits of an adolescent woman who takes up writing as a mode of self-examination. The author shares a moving portrait of Kasturba Gandhi’s illness and death and also unravels the deep emotional bond she develops with Gandhi, whom she calls her ‘mother’.